Science through children's literature : an integrated approach - Butzow, Carol M., 1942-; Butzow, John W., 1939- (Englewood, Colo. : Teacher Ideas press, 2000)
Contains over thirty instructional units which show teachers how to use famous children's books to introduce their students to the life, earth, and physical sciences.
Integrating science and reading -- Teaching the integrated unit -- Trees -- Seeds -- Reproduction and development -- Ducks and other birds -- Ants and other insects -- Spiders -- Ladybugs -- Fish -- Reptiles -- Air pollution -- Adaptations of animals -- Nutrition -- The ear and hearing -- Territorial and environmental ownership -- Volcanoes -- Rocks -- Soil -- Lighthouses and oceans -- Mussels and Arctic life -- Astronomy and outer space -- Weather and seasons -- The eye, vision, and optics -- Shadows and light -- Shapes -- Measurement -- Energy and motion -- Buoyancy -- Force and movement -- Chemical and physical change -- Balloons -- Airplanes.
Includes bibliographical references and index.
Reference and Research Book News.
Science Books & Films (A.A.A.S.).
Professional
Keywords: Activity programs in education; Children -- Books and reading; Science -- Study and teaching (Elementary); Children -- Books and reading; Science -- Study and teaching